PENERAPAN TAUHID DALAM SISTEM ZAKAT SEBAGAI INSTRUMEN KESEJAHTERAAN UMAT - Nurul Hasannah; Nabila Shaqna Wanayu; Vivi Syahfitri; Madinauli Novita Sinaga; Adam Fahlendri; Fikhar Ihsan; Ismail Fadly Dalimunthe; Miftahul Fadli; Ferizal (CV. BAROKAH PUBLISHER, 2026)
The application of tauhid in the zakat system as a welfare instrument emphasizes zakat's spiritual and social dimensions. Obligatory in Islam, zakat not only fulfills financial duties but also serves as an effective wealth redistribution tool, fostering solidarity and reducing economic inequality. Professionally and accountably managed, zakat can alleviate poverty, especially through the productive zakat concept, which focuses on empowering mustahik economically. Integrating tauhid values into zakat management policies ensures justice and social responsibility while increasing participation in zakat fulfillment. Furthermore, transparency in zakat management strengthens trust in zakat institutions, encouraging greater community contributions. Through the principles of tauhid, zakat has the potential to create a more equitable, self-reliant, and prosperous society.